2006
DOI: 10.1097/01.ta.0000231768.44727.a2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Anemia and Transfusion in Traumatic Brain Injury

Abstract: Patients with severe TBI should not have a different transfusion threshold than other critical care patients. Prospective studies are needed to evaluate the effects of anemia in TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 21 publications
(15 reference statements)
4
71
0
8
Order By: Relevance
“…During anemia, CBF increases as a result of improved rheology of the blood flow in the cerebral vessels and as a compensatory response to decreased oxygen delivery [57]. While some data suggests that hematocrit < 30% is associated with worse discharge Glasgow Outcome Scale scores in adults with severe TBI [58], neither the optimal duration for maintaining a specific hemoglobin level, nor the relationship between target transfusion and neurological outcome are fully known [59]. A recent study of critically ill children demonstrated that maintaining hemoglobin of 7 g/dl rather than 9.5 g/dl can reduce requirements for blood transfusion, but none of these subjects had TBI [60].…”
Section: Control Of the Cerebral Circulationmentioning
confidence: 99%
“…During anemia, CBF increases as a result of improved rheology of the blood flow in the cerebral vessels and as a compensatory response to decreased oxygen delivery [57]. While some data suggests that hematocrit < 30% is associated with worse discharge Glasgow Outcome Scale scores in adults with severe TBI [58], neither the optimal duration for maintaining a specific hemoglobin level, nor the relationship between target transfusion and neurological outcome are fully known [59]. A recent study of critically ill children demonstrated that maintaining hemoglobin of 7 g/dl rather than 9.5 g/dl can reduce requirements for blood transfusion, but none of these subjects had TBI [60].…”
Section: Control Of the Cerebral Circulationmentioning
confidence: 99%
“…При более низком уровне транспорт кислорода уменьшается без заметного изменения вязкости крови, а при уровне более 0,30 -вязкость повышается непропорцио-нально транспорту кислорода. Впрочем, в последних исследованиях отмечено, что низкий уровень гема-токрита также допустим, в настоящее время прием-лемой считают его величину 0,21-0,30 [77][78][79].…”
Section: лечебные мерыunclassified
“…Como en otros subgrupos de pacientes de UCI, parece que podrían ser seguras tasas menores 54,55 , aunque todavía está pendiente determinar el nivel óptimo y en qué fase de la evolución.…”
Section: Manejo De La Presión De Perfusión Cerebralunclassified